The Preference of Women and Men Regarding Female Genital Depilation - Sangiorgi, Maria Luiza Prudente de Oliveira; Lara, Lucia Alves da Silva; Lerri, Maria Rita; Ferriani, Rui Alberto; Romão, Adriana Peterson Mariano Salata (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Purpose To evaluate the preferences of women and men regarding female pubic hair depilation and identify possible reasons for these preferences.Methods This is a cross-sectional study of men and women over 18 years old who were invited by the official blog of our institution to respond anonymously to an online and self-administered questionnaire made by the researchers. The analyses were made using the Statistical Analysis System (SAS, SAS Inc., Cary, NC, US) software, version 9.3, and contingency tables were used to verify the distribution of variables. The univariate statistical analysis was performed using the Pearson chi-squared test, and the differences for values of p < 0.05 were considered significant.Results We obtained data from 69,920 subjects (52,787 women and 17,133 men). The mean age was 31.9 years for men, and 28.5 years for women. Most women (64.3%) and men (62.2%) preferred complete removal of female pubic hair, and this preference was more pronounced in younger women and men. Most women reported performing depilation at home (55.8%), with 44.4% using hot wax and 40.1% using a razor blade. About half of the women (44.7%) and men (50.1%) reported sexual activity, having intercourse 2 to 3 times per week. The frequency of intercourse and sexual satisfaction in women correlated with total pubic hair removal.Conclusion Most Brazilian women and men prefer the complete removal of female pubic hair, especially those who are younger and more sexually active. Women who are satisfied with the appearance of their own genitalia have a stronger preference for complete removal of pubic hair.
Keywords: depilation; hair removal; genitalia; sexuality; internet; sexual behavior